The Correlation between Self-Efficacy Levels and Pedagogical Content Knowledge among Madrasah Ibtidaiyah Teachers - Ifada Novikasari; Donny Khoirul Azis; Noor Elebiary (Universitas Islam Negeri (UIN) Salatiga, 2024)
This study examines the relationship between self-efficacy in geometry and Pedagogical Content Knowledge (PCK) among Madrasah Ibtidaiyah teachers in Banyumas Regency. Self-efficacy was assessed in 79 sampled teachers using a multidimensional teaching self-efficacy scale focused on effectiveness and classroom management, while PCK was evaluated through tasks involving the perimeter and area of two-dimensional shapes. The findings reveal a weak correlation between self-efficacy and PCK, indicating limited interdependence. This highlights the need to address gaps in both areas. Within an Islamic context, the study emphasizes the relevance of tazkiyah (self-purification) and ilm (knowledge acquisition) as principles of teacher development. It recommends targeted training aligned with Islamic values to simultaneously enhance self-efficacy and PCK. Such an integrated approach aims to improve teaching skills, foster holistic growth, and create a nurturing learning environment that benefits both teachers and students.